Analisa Servis dalam Pertandingan Final Bola Voli Putra Pada Event Proliga - Muhammad Zaim Zen; Febriyan Dwi Cahyono; Faisol Hamid; Yully Wahyu Sulistyo (SPRINTER: Jurnal Ilmu Olahraga, 2025)
PROLIGA is one of the professional volleyball events in Indonesia. Volleyball itself has entered the elite level of sports that are in high demand. Serving is one of the efforts or techniques used in volleyball. This study aims to analyse serves in competitive matches. The research method involved analysing every serve made in the 2023 PROLIGA Men's Volleyball Final through match observation on the official website. The serves analysed were successful serves, serve errors or serves out, and serve points. The success rate of serves in this final match was high, at around 73%, but the success rate of scoring points from serves was less than 17%. The conclusion from the results of this study is that failed serves and easy serves are the two biggest disadvantages in winning volleyball matches, especially at higher or professional levels of competition.